Implementing Scrum in Executive Information System at University - Setiawan, Ridwan; Mulyani, Asri; Fitriani, Pipit; Gusti, Kharisma Wiati (Politeknik Ganesha Medan, 2024)
Executive Information System is a type of system that provides information about reports generated by the system, assists executives in making necessary decisions, and provides easy access to information from both internal and external sources. This system aims to help specific organizations solve problems. The objective of this research is to design and develop a web-based executive information system that can provide access to student, faculty, and program data at the Faculty of Economics, Garut University, with data visualization in the form of graphs and numbers using the Scrum method. The Executive Information System can provide a real-time overview of data for executive-level individuals, namely the faculty leaders. Scrum is the development methodology used, with stages such as product backlog, sprint, daily scrum meeting, sprint review, and sprint retrospective. The results of this research have produced an Executive Information System that provides data on students, faculty, and programs. This system features functions such as filtering, drilldown, and importing. Testing results indicate the successful achievement of sprints on time or even ahead of schedule, and the team was able to meet targets in each sprint. In this research, the Scrum method has been effectively utilized in creating the executive information system. Therefore, this method can be employed to develop similar executive information systems in the future.